2018
DOI: 10.1155/2018/1926308
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Incidence of Prediabetes or Type 2 Diabetes: A Four-Year Follow-Up Community-Based Study

Abstract: Aim To examine whether the baseline 25-hydroxyvitamin D [25(OH)D] level was predictive of the onset of prediabetes or type 2 diabetes (T2DM) in the Chinese population. Methods This was a 4-year follow-up study that was conducted in the Chengdu region of China as part of the China National Diabetes and Metabolic Disorders Study. The study included 490 participants that were free of prediabetes and type 2 diabetes mellitus (T2DM) at baseline and had complete data by follow-up examinations. Glucose, insulin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Conversely, in a four-year follow-up study, decreased 25(OH)D levels were significantly associated with the risk of developing prediabetes (OR: 3.01, 95% CI: 1.50–6.06, p = 0.002) and type2 DM (OR: 5.61, 95% CI: 1.73–18.27, p = 0.004) [29]. Moreover, low baseline 25(OH)D levels were an independent predictor of increased IR [29]. Additionally, recent meta-analyses have shown that Vit D supplementation reduces insulin resistance in selected patient series [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a four-year follow-up study, decreased 25(OH)D levels were significantly associated with the risk of developing prediabetes (OR: 3.01, 95% CI: 1.50–6.06, p = 0.002) and type2 DM (OR: 5.61, 95% CI: 1.73–18.27, p = 0.004) [29]. Moreover, low baseline 25(OH)D levels were an independent predictor of increased IR [29]. Additionally, recent meta-analyses have shown that Vit D supplementation reduces insulin resistance in selected patient series [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have also shown that low 25(OH)D levels are associated with the development of insulin resistance and incident T2DM . In 490 healthy adults in China, lower serum 25(OH)D levels at baseline were significantly associated with the development of prediabetes and T2DM after a 4‐year follow‐up . A meta‐analysis of cross‐sectional and longitudinal studies in patients with T2DM ( n = 71 studies) and non‐diabetic individuals ( n = 28 studies) also found that serum 25(OH)D levels were inversely correlated with fasting glucose and insulin resistance, both in patients with T2DM and in non‐diabetic participants, although the relationship was more pronounced in those with T2DM .…”
Section: Vitamin D and Type 2 Diabetesmentioning
confidence: 97%
“…Vitamin D deficiency has become a common health problem in China, especially in patients with IFG and T2DM [ 5 ]. Numerous studies have investigated the associations between vitamin D and IFG or T2DM, however, the results are controversial [ 6 , 7 , 8 , 9 , 10 ], and the underlying mechanisms are unclear. For instance, a prospective cohort study with 29 years of follow-up found that low 25(OH)D levels increased the risk of T2DM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%